Current issues in the treatment of adolescent idiopathic scoliosis: a comprehensive narrative review - Kim, Hyoungmin; Chang, Bong-Soon; Chang, Sam Yeol (Asian spine journal, 2024)
Adolescent idiopathic scoliosis (AIS) is a three-dimensional deformity of unknown etiology that commonly affects adolescents, imposing significant socioeconomic burdens. Effective management necessitates a comprehensive approach that takes into account multiple factors, including growth potential and psychological issues. Despite significant advancements in AIS management, several questions regarding optimal treatment strategies persist. Recent technological advancements are transforming the treatment landscape, encompassing advancements in bracing, robotic-assisted deformity corrections, and other interventions. This review explores current issues debated in the literature concerning the treatment of AIS, focusing on contemporary high-level evidence (e.g., meta-analyses and randomized controlled trials). Furthermore, this review explores cutting-edge developments and future directions in AIS management, including the integration of artificial intelligence and augmented reality.